ANALISIS SPIRITUAL CHARACTER PELAKU ISBAT NIKAH DI PENGADILAN AGAMA WATAMPONE - A. Sri Mardiyanti Syam (Institut Agama Islam Negeri Bone, 2021)
AbstractRegarding the marriage legalization cases in the Religious Court of Watampone, if the formal requirements have been met, then the religious court by the judges will make a verdict or decision of which written